Human Pluripotent Stem Cell Culture: Current Status, Challenges, and Advancement - Sushrut Dakhore; Bhavana Nayer; Kouichi Hasegawa (Hindawi Limited, 2018)
Over the past two decades, human embryonic stem cells (hESCs) have gained attention due to their pluripotent and proliferative ability which enables production of almost all cell types in the human body in vitro and makes them an excellent tool to study human embryogenesis and disease, as well as for drug discovery and cell transplantation therapies. Discovery of human-induced pluripotent stem cells (hiPSCs) further expanded therapeutic applications of human pluripotent stem cells (PSCs). hPSCs provide a stable and unlimited original cell source for producing suitable cells and tissues for downstream applications. Therefore, engineering the environment in which these cells are grown, for stable and quality-controlled hPSC maintenance and production, is one of the key factors governing the success of these applications. hPSCs are maintained in a particular niche using specific cell culture components. Ideally, the culture should be free of xenobiotic components to render hPSCs suitable for therapeutic applications. Substantial efforts have been put to identify effective components, and develop culture conditions and protocols, for their large-scale expansion without compromising on quality. In this review, we discuss different media, their components and functions, including specific requirements to maintain the pluripotent and proliferative ability of hPSCs. Understanding the role of culture components would enable the development of appropriate conditions to promote large-scale, quality-controlled expansion of hPSCs thereby increasing their potential applications.